The Peace Dividend : Military Spending Cuts and Economic Growth - Knight, Malcolm; Loayza, Norman; Villanueva, Delano (Washington, D.C. : International Monetary Fund, 1995)
Although conventional wisdom suggests that reducing military spending may improve a country's economic growth performance, empirical studies have produced ambiguous results. This paper extends a standard growth model and estimates it using techniques that exploit both cross-section and time-series dimensions of available data to obtain consistent estimates of the growth-retarding effects of military spending via its adverse impact on capital formation and resource allocation. Model simulations suggest that a substantial long-run 'Peace Dividend'--in the form of higher capacity output--may result from: (i) markedly lower military expenditure levels achieved in most regions during the late 1980s; and (ii) further military spending cuts that would be possible in the future if a global peace could be secured.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet